2007
DOI: 10.1073/pnas.0606514104
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate expression and functional profiling identify an extracellular proteolytic signaling pathway

Abstract: A multidisciplinary method combining transcriptional data, specificity profiling, and biological characterization of an enzyme may be used to predict novel substrates. By integrating protease substrate profiling with microarray gene coexpression data from nearly 2,000 human normal and cancerous tissue samples, three fundamental components of a protease-activated signaling pathway were identified. We find that MT-SP1 mediates extracellular signaling by regulating the local activation of the prometastatic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
115
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 37 publications
5
115
0
Order By: Relevance
“…The existence of interactions between CDCP1 and matriptase is also supported by a recent report showing that these proteins co-immunoprecipitate from SW480 and SW620 colon cancer cell lysates using an antibody against the tetraspanin CD9 (35). In addition, it has been reported that the mRNA expression patterns of this protease:substrate pair are significantly correlated in many tissue types (38). It has also been shown in separate reports that both matriptase (39) and CDCP1 (12) are expressed during prostate cancer progression.…”
Section: Discussionsupporting
confidence: 57%
“…The existence of interactions between CDCP1 and matriptase is also supported by a recent report showing that these proteins co-immunoprecipitate from SW480 and SW620 colon cancer cell lysates using an antibody against the tetraspanin CD9 (35). In addition, it has been reported that the mRNA expression patterns of this protease:substrate pair are significantly correlated in many tissue types (38). It has also been shown in separate reports that both matriptase (39) and CDCP1 (12) are expressed during prostate cancer progression.…”
Section: Discussionsupporting
confidence: 57%
“…10,36 Indeed, Hgfac knockout mice also showed enhanced susceptibility to DSS-induced colitis, possibly due to insufficient activation of HGF after acute mucosal injury. 37 Interestingly, a recent gene-centric mapping analysis suggests that the MST1 gene encoding MSP, which is another cytokine activated by HGFAC and matriptase, 38,39 may be involved in IBD pathogenesis. 40 Therefore, altered pericellular activation of MSP may also be involved in the susceptibility of HAI-1/SPINT1-deficient mice to DSS colitis.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The surface of metazoan organs is lined by specialized epithelia that are endowed with multiple general and organ-specific functions. These include the maintenance of ion gradients, macromolecular transport, absorption, secretion of lipids, mucins, hormones and growth factors, and exclusion of pathogens.…”
mentioning
confidence: 99%